(3GdLhGgQ GdMSGf hTeS YjO GdReGf aj Yde GdbHGfs - (3GdbHGfj , NVQ Hf YHO GdQMef Hf CMeO Hf Ydj GdHQdSj,J (B853 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd MVQJ Hf YHO GdbGOQ Ef CTQa GdYdhe eG jejR Hg Hf GdMb hGdHGWd hGdeSJbje hGdeGFd s
(3BNQgG (B:s
(3jMUd Kbd GdYehO Ch GdSba Ch GdMGFW hfMh Pdc hGddg SHMGfg hJYGdi CYde GfJgi s
(3GdfSNI HgG MhGTs
(3Hg ebGHdIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B307s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs